2000
DOI: 10.1046/j.1464-410x.2000.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum vascular endothelial growth factor in patients with hormone‐escaped prostate cancer

Abstract: Objective To investigate the role of serum vascular endothelial growth factor (VEGF) in the assessment of patients with prostate cancer. Patients, subjects and methods Serum from 78 men was assayed for VEGF using a commercially available enzyme‐linked immunosorbent assay kit. Forty‐eight patients had a histopathological diagnosis of prostate cancer (16 local disease, 32 metastatic), nine had benign prostatic hyperplasia (BPH) and 21 were healthy controls. Results The mean serum VEGF level was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Details for each of these studies are given in Supplementary Table S1 for breast cancer (Yamamoto et al, 1996;Obermair et al, 1997;Salven et al, 1997Salven et al, , 1999bVerheul et al, 1997;Eppenberger et al, 1998;Adams et al, 2000;Foekens et al, 2001;Heer et al, 2001;Colleoni et al, 2002;Toi et al, 2002;Caine et al, 2003;Manders et al, 2003;Desruisseau et al, 2004;Granato et al, 2004;Sancak et al, 2004;Zhao et al, 2004;Bando et al, 2005;O'Riain et al, 2005), Supplementary Table S2 for prostate cancer (Joseph et al, 1997;Salven et al, 1997;Bauer et al, 1999;Duque et al, 1999;Jones et al, 2000;Bok et al, 2001;Figg et al, 2001;Caine et al, 2003Caine et al, , 2004Kohli et al, 2003;George et al, 2004;Kaushal et al, 2005;Li et al, 2005), Supplementary Table S3 for colorectal cancer (Dirix et al, 1996;Hyodo et al, 1998;Kumar et al, 1998;Baker et al, 2000;Chin et al, 2000;Davies et al, 2000;George et al, 2000;Broll et al, 2001;...…”
Section: Study Selectionmentioning
confidence: 99%
“…Details for each of these studies are given in Supplementary Table S1 for breast cancer (Yamamoto et al, 1996;Obermair et al, 1997;Salven et al, 1997Salven et al, , 1999bVerheul et al, 1997;Eppenberger et al, 1998;Adams et al, 2000;Foekens et al, 2001;Heer et al, 2001;Colleoni et al, 2002;Toi et al, 2002;Caine et al, 2003;Manders et al, 2003;Desruisseau et al, 2004;Granato et al, 2004;Sancak et al, 2004;Zhao et al, 2004;Bando et al, 2005;O'Riain et al, 2005), Supplementary Table S2 for prostate cancer (Joseph et al, 1997;Salven et al, 1997;Bauer et al, 1999;Duque et al, 1999;Jones et al, 2000;Bok et al, 2001;Figg et al, 2001;Caine et al, 2003Caine et al, , 2004Kohli et al, 2003;George et al, 2004;Kaushal et al, 2005;Li et al, 2005), Supplementary Table S3 for colorectal cancer (Dirix et al, 1996;Hyodo et al, 1998;Kumar et al, 1998;Baker et al, 2000;Chin et al, 2000;Davies et al, 2000;George et al, 2000;Broll et al, 2001;...…”
Section: Study Selectionmentioning
confidence: 99%
“…The density of new vessel growth is associated with clinically aggressive prostate cancer and disease progression (23). It has been reported that higher levels of VEGF are present in the serum and plasma of men with prostate cancer compared with healthy controls, and increased VEGF levels are associated with metastatic disease and biochemical progression (24,25). A recent meta-analysis has shown that VEGF levels in serum or plasma are ∼2.18 and 1.85 times greater (weighted average of all cancer studies analyzed), respectively, in prostate cancer patients versus healthy controls (26).…”
mentioning
confidence: 99%
“…Other studies (7)(8)(9)(10)13,14) showed higher VEGF levels in patients with prostate cancer when compared with healthy controls or subjects with benign prostatic hypertrophy. Such comparisons however, are not clinically relevant since elevated tPSA is the most frequent indication for prostatic biopsy, and reflect limited-challenge-bias (16,17).…”
Section: Commentsmentioning
confidence: 97%
“…Some authors have found higher levels of VEGF in prostatic cancer patients (7)(8)(9)(10), while others found no differences between subjects with benign prostatic hyperplasia (BPH) and those with malignant disease (11,12), or increased values only in patients with metastatic prostatic cancer (13) or hormonerefractory disease (14). However, most previous studies evaluated relatively small samples (8,9,(11)(12)(13)(14) and all suffered from limited-challenge bias, as prostatitis, which may interfere with the diagnostic value of VEGF, was not evaluated separately in any of the studies and in many studies the control group only included subjects with no suspicion of prostatic cancer (7,10,13).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%